Characteristics of open eye injuries in the Beirut Port explosion. Issue 9 (September 2021) - Sukkarieh, Georges; Lahoud, Corinne; Ghorayeb, Ralph; Abi Karam, Mariana; Succarieh, Yara; Saleh, Maher; Jalkh, Alexandre
Highlights: Ocular injuries secondary to explosions occurs indoors, near windows and less than 500m away from the explosion site. To reduce the number of eye injuries occurring during explosions, civilians should be educated that during a blast one should walk away from windows and should cover his eyes to protect them from fear of a projectile injuring his eyes. Another measure to undertake is that tempered glass, which breaks into small pieces, should replace regular glass in all buildings. Abstract: Introduction: On the 4 th of August 2020 an ammonium nitrate explosion took place at the Port of Beirut in Lebanon. The aim of this study was to present the open eye injuries caused by the Beirut Port blast, and to describe their characteristics and visual outcomes at 6 months. Methods: Patients who suffered from open globe injuries during the Beirut port explosion were recruited. Characteristics of the ocular injuries and best corrected distance visual acuity (BCVA) were recorded at presentation and at 6 months. Results: All included eyes (23 eyes of 19 patients) suffered from penetrating open globe injuries secondary to glass material and were operated by globe exploration + primary repair. Four of the 19 patients suffered from bilateral injuries none of whom suffered from legal blindness. BCVA at presentation was hand motion or worse in 21 of 23 eyes (91%). Seven of 23 eyes (30%) had expulsive loss of intraocular tissue, 4 of 23 eyes (17%) had retinal detachment and 4 of 23 eyes (17%) had traumatic cataracts. Ocular trama score (OTS) had a mean +/- standard deviation (SD) of 61 +/- 12. Eleven of 23 eyes (48%) had zone 2 ocular injuries and 10 of 23 eyes (43%) had zone 3 ocular injuries. At 6 months follow-up 15 of 23 eyes (65%) had a BCVA of less than 20/200. All patients with Grade 2 OTS, zone 3 injuries, expulsive loss of intraocular tissue and retinal detachment had BCVA of less than 20/200 at 6 months. Conclusion: Open eye injuries secondary to explosions occur most frequently due to glass fragments. Most of the victims were indoors, near windows and less than 500m away of the explosion site at the time of the blast. The majority of victims have very low BCVA, a low OTS and a high ocular ZOI at presentation which reflects the danger of open globe injuries secondary to blasts. A high ZOI, a low OTS, the expulsive loss of intraocular tissue and retinal detachment seem to be predictors of worse VA at 6 months.